2008
DOI: 10.1016/j.psyneuen.2007.11.011
|View full text |Cite
|
Sign up to set email alerts
|

Limited effects of β-endorphin compared to loperamide or fentanyl in a neuroendocrine biomarker assay in non-human primates

Abstract: SummaryThe in vivo pharmacodynamics of the opioid neuropeptide β-endorphin (a major endogenous agonist at the μ-opioid receptor) are difficult to determine in non human primate models with translational value, or in humans. The present studies therefore employed a neuroendocrine biomarker assay, prolactin release, to systematically compare the in vivo profile of i.v. β-endorphin (0.01-0.32 mg/ kg; i.v.) in gonadally intact male rhesus monkeys (n=4) to that of the peripherally selective μ-agonist loperamide (0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 52 publications
2
9
0
Order By: Relevance
“…The selected dose ranges for loperamide and tariquidar were consistent with studies that focused on their pharmacodynamic profile in humans or nonhuman primates, including PET studies of P-glycoprotein function (Butelman et al, 2008;Wagner et al, 2009;Bauer et al, 2010;Kreisl et al, 2010). The similarity of these conditions is supportive of the translational value of these simple behavioral and CNS penetration measures (see below) as endpoints to study P-glycoprotein modulation in vivo.…”
Section: Discussionsupporting
confidence: 64%
“…The selected dose ranges for loperamide and tariquidar were consistent with studies that focused on their pharmacodynamic profile in humans or nonhuman primates, including PET studies of P-glycoprotein function (Butelman et al, 2008;Wagner et al, 2009;Bauer et al, 2010;Kreisl et al, 2010). The similarity of these conditions is supportive of the translational value of these simple behavioral and CNS penetration measures (see below) as endpoints to study P-glycoprotein modulation in vivo.…”
Section: Discussionsupporting
confidence: 64%
“…These data are consistent with the in vitro profile of herkinorin, which shows relative (approximately 8-fold) binding selectivity for μ- over κ- receptors (Harding et al, 2005). As a direct confirmation in this setting, the smaller dose of nalmefene (0.01 mg/kg) was indeed sufficient to cause complete blockade of the effects of the selective μ-agonist fentanyl (see also Butelman et al, 2008). This confirms that an agonist thought to act solely through μ-receptors in this assay is fully blocked by the smaller nalmefene dose under these experimental conditions.…”
Section: Discussionmentioning
confidence: 66%
“…compared to repeated vehicle injection, for control purposes. The effects of loperamide (0.01-0.32 mg/kg males and females) and salvinorin A (0.001-0.032 mg/kg [males] and 0.00032-0.01 mg/kg [females], based on prior studies; Butelman et al, 2007; Butelman et al, 2008) were also studied under identical cumulative dosing procedures.…”
Section: Designmentioning
confidence: 99%
See 1 more Smart Citation
“…Veening et al, also reported that half-life values of b-endorphin vary from 20 to 50 min in the human circulation [34]. Butelman et al, reported that full-length b-endorphin was detectable in all subjects up to 5 minutes after intravenous administration [37]. Moreover, Bruehl et al, reported that chronic pain may initially be associated with upregulation of endogenous opioid analgesic systems, which then may become dysfunctional over time [38].…”
Section: Discussionmentioning
confidence: 99%